(untitled) (JS (JURNAL SEKOLAH), 2021)
Abstract: This classroom action research is motivated by the low learning outcomes of students. The achievement of theme 8 scores for fourth grade students at SDN Kumesu 02 still received scores below the Minimum Completeness Criteria (KKM) of 70. Of the 12 students, only 5 (41.66%) got an average score above the KKM. While the remaining 7 students (58.33%) still scored below the KKM. This study aims to improve learning outcomes of the theme 8 My Living Areas through the PBL model with audiovisual media for fourth grade students of SD Negeri Kumesu 02. This research is a classroom action research conducted in three cycles consisting of two meetings each cycle. Data collection techniques in student research, data collection techniques used in this study were documentation, observation, interviews, and tests. The results of this study are proven to be able to improve student learning outcomes in learning the theme of 8 My Living Areas. In the third cycle, the minimum completeness criteria completeness was 83.33% with an average achievement of 80.41. It can be concluded that student learning outcomes have increased from cycle I to cycle III. Keywords: Learning Outcomes, Problem Based Learning Model, Audiovisual Media Abstrak: Penelitian tindakan kelas ini dilatar belakangi oleh hasil belajar pada peserta didik yang masih rendah. Pencapaian nilai tema 8 pada siswa kelas IV SDN Kumesu 02 masih banyak yang mendapatkan nilai dibawah Kriteria Ketuntasan Minimal (KKM) yaitu 70. Dari jumlah 12 siswa hanya 5 anak (41,66%) yang mendapat nilai rata-rata diatas KKM. Sedangkan sisanya sebanyak 7 orang siswa (58,33%) masih mendapat nilai dibawah KKM. Penelitian ini bertujuan untuk meningkatkan hasil pembelajaran tema 8 Daerah Tempat Tinggalku melalui model PBL dengan media audiovisual pada siswa Kelas IV SD Negeri Kumesu 02. Penelitian ini merupakan penelitian tindakan kelas yang dilaksanakan dengan tiga siklus terdiri dari dua kali pertemuan tiap siklus. Teknik pengumpulan data pada penelitian peserta didik, teknik pengumpulan data yang digunakan dalam penelitian ini adalah dokumentasi, observasi, wawancara, dan tes. Hasil penelitian ini terbukti dapat meningkatkan hasil belajar peserta didik pada pembelajaran tema 8 Daerah Tempat Tinggalku. Pada siklus III dengan ketuntasan KKM sebesar 83,33% dengan capaian rata-rata yang diperoleh sebesar 80,41. Dapat disimpulkan bahwa hasil belajar peserta didik mengalami peningkatan mulai dari siklus I sampai siklus III. Kata Kunci : Hasil Belajar, Model Problem Based Learning, Media audiovisual